Intervensi farmasis didokumentasikan untuk membandingkan intervensi aktif farmasis di bangsal berbeda di rumah sakit anak, dan untuk membandingkan faktor yang mempengaruhi penerimaan intervensi farmasis oleh dokter. Peneliti melakukan observasi intervensi - HESTY UTAMI RAMADANIATI; YA PING LEE; JEFFERY DAVID HUGHES (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Pharmacists’ interventions were documented to compare pharmacists’ active interventions in different settings within a children’s hospital and identify the predictors for physician acceptance of the interventions. The investigator observed pharmacists’ interventions between 35-37 days on five study wards. The rates and types of pharmacists’ interventions on the different wards were compared. Multivariate logistic regression analysis was performed to identify the acceptance predictors of the interventions. The Hematology-Oncology Ward had a higher rate of active interventions (2.43 interventions per 100 medication orders) compared to general settings. Dose adjustment was the most frequent interventions in the general settings, whilst drug addition constituted the most common interventions on the Hematology-Oncology. The acceptance degree of intervention by physicians was high. There were three variables predicting the acceptance: patients’ age (OR = 0.893; 95%CI 0.813, 0.981), non high-risk medication (OR = 2.801; 95% CI 1.094, 7.169) and pharmacists’ experience (OR = 1.114; 95%CI 1.033, 1.200). The rate of active interventions on Hematology-Oncology Ward was higher than the general wards.The pattern of the interventions on Hematology-Oncology Ward was different compared to that of other wards. The interventions involving younger patients, non high-risk medications, recommended by more experienced pharmacists increased likelihood of acceptance by physicians.